Managing technology development teams – exploring the case of microsytems and nanosystems. (26th February 2013) - Burger, Norbert; Staake, Thorsten; Fleisch, Elgar; Hierold, Christofer
<x xml:space="preserve">Abstract</x> New sensor and actuator concepts based on microelectromechanical systems (MEMS) and nanoelectromechanical systems (NEMS) are increasingly being developed from lab status toward commercialization. The associated technology development for the provision of improved functionalities and cost reduction often requires highly interdisciplinary development teams where scientists and engineers from different disciplines closely work together. Managing these teams is a key challenge for MEMS/NEMS organizations. This research examined eight technology developments in MEMS/NEMS in international companies. Based on in‐depth interviews with innovators, we explored the managerial aspects of development teams. We identified and discuss (1) leadership, (2) market, (3) team structure and culture, (4) innovation motivation, (5) innovation driver, (6) experience and know‐how, and (7) product vision and innovation strategy as key influences on teams in the early development phases of MEMS/NEMS. Our study reveals that integrative and manufacturing know‐how and capabilities are the most critical capacities to be developed by the team from the idea to the concept phase. The team's lived experience during long development times from 5 to 10 years or more may allow a fast response to changes from market and technology (e.g. materials and nanotechnology). The results indicate that the process of how know‐how and capabilities are created by the team is more important than the mere existence of specific expertise.